2020
DOI: 10.1007/s42729-020-00362-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Balance of Farming Systems in Tigray, Northern Ethiopia

Abstract: The purpose of this study was to explore how soil fertility management and farm nutrient balances varied across socio-economic groups in northern Ethiopia. Field surveys were carried out in 32 farms in Tigray, northern Ethiopia using different socioeconomic groups, viz.: model/non model and female/male farmers. The nutrient input flows and output flows were monitored and analysed using Monitoring for Quality Improvement (MonQI) toolbox. Results of the study showed that average nitrogen (N), phosphorus (P) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 63 publications
1
17
1
Order By: Relevance
“…Similarly, the lowest BD in the lower slope position in Yigossa Watershed, Northwestern Ethiopia, is reported by Gebreslassie et al (2014) due to the higher clay content and organic matter accumulation at the upstream positions. Corresponding to our result, significantly (p < 0.001) higher BD in the highland areas compared to the lowland areas have also been reported by Gebresamuel et al (2020) in northern Ethiopia. Besides, BD was found linearly correlated among land use across elevation except under grassland, which was inconsistent (Figure 4).…”
Section: Soil Bulk Density and Som Concentration In Different Land-uses Across Elevationsupporting
confidence: 90%
“…Similarly, the lowest BD in the lower slope position in Yigossa Watershed, Northwestern Ethiopia, is reported by Gebreslassie et al (2014) due to the higher clay content and organic matter accumulation at the upstream positions. Corresponding to our result, significantly (p < 0.001) higher BD in the highland areas compared to the lowland areas have also been reported by Gebresamuel et al (2020) in northern Ethiopia. Besides, BD was found linearly correlated among land use across elevation except under grassland, which was inconsistent (Figure 4).…”
Section: Soil Bulk Density and Som Concentration In Different Land-uses Across Elevationsupporting
confidence: 90%
“…Soil N balances in this study are lower, whereas P balances are higher (Table 3), than values reported in different parts of Ethiopia (Elias, 2002;Gebresamuel et al, 2020;Haileslassie et al, 2007;Stoorvogel & Smaling, 1990;Van Beek et al, 2016). Meaning that, soil nutrient balances reported in the literature are more negative than those in this study.…”
Section: Effects Of Soil Amendments On Soil Nutrient Balancescontrasting
confidence: 76%
“…difference in magnitude was on account of the full nutrient balance in the other studies and the larger scale of study areas [32]. The positive balance of P could be due to the DAP fertilizer with the soil being naturally enriched with P while the negative balance of N and K could be related to the leaching due to high rainfall, use of crop residues for feed and fuel, and potassium fertilizer not being available, which indicates overexplotation [33].…”
Section: Plos Watermentioning
confidence: 86%